Zakat Institutions and Universities Strategic Partnership for Poverty Alleviation - Abu baker Ramadan Hussain (International Journal of Zakat, 2019)
Despite the global efforts to eradicate poverty around the world, avoid exists in the literature examining the role of effective strategic partnership between universities and Zakat institutions as a core social protection provider in the Muslim world. This paper contributes to the literature in this area by assessing the prevailing patterns of collaboration between Zakat organizations and universities. The main objective is two folds; first, by appraising their potentialities, it establishes common interests that focus on shared goals and objectives; ethics and values; and networks and processes. The second, is to propose strategic partnership framework. The proposed strategic partnership framework will increase penetration and outreach by bridging knowledge gap, better targeted social protection components and improving communication and networks. The adoption of the framework will change how these institutions approach their goals and respond to community pressures providing variety of differentiated products and services to reduce poverty.